Rivaroxaban: searching the integral vascular protection. Issue 7 (3rd July 2018) - Barrios, Vivencio; Almendro-Delia, Manuel; Facila, Lorenzo; Garcia-Moll, Xavier; Mazón, Pilar; Camafort, Miguel; Cepeda, José María; Mediavilla Garcia, Juan Diego; Pose Reino, Antonio; Suarez Fernandez, Carmen
ABSTRACT: Introduction : Residual cardiovascular risk remains high in patients with atherosclerotic cardiovascular disease despite current antithrombotic therapy. On the other hand, patients with atrial fibrillation have an increased risk of myocardial infarction and cardiovascular death. As a result, a new antithrombotic approach appears necessary to reduce this risk. Areas covered : In this article, the role of rivaroxaban on vascular protection in patients with cardiovascular disease and/or atrial fibrillation was reviewed, with a particular focus, but not limited, on clinical trials. Expert commentary : Previous data have shown that factor Xa plays a key role in the etiopathogenesis of atherothrombosis. Experimental data suggest that rivaroxaban exhibits antiinflammatory and antioxidative stress properties, and may improve endothelial dysfunction. The COMPASS trial showed that among patients with stable atherosclerotic vascular disease, the addition of rivaroxaban 2.5 mg twice daily (vascular dose) to aspirin provided a higher cardiovascular protection than aspirin alone. In ROCKET-AF trial, compared with warfarin, rivaroxaban 20 mg once daily (15 mg if moderate renal dysfunction) (anticoagulant dose) was, at least, as effective as warfarin for the prevention of stroke or systemic embolism among patients with nonvalvular atrial fibrillation, with a trend toward a reduction in the risk of cardiovascular outcomes. All these data suggest that rivaroxaban might have a vascular protective effect beyond its stroke/systemic embolism preventive activity.